The internet as interpersonal media: Case of Serbia - Petrović Dalibor (Sociologija, 2013)
Bearing in mind that modern technological tools for communication play an integral role in sustaining of social relationships, the aim of this article is to determine whether the internet has been replacing face to face (FtF) contacts in sustaining interpersonal relationships and are there some aspects of personal networks contact that are handled by interpersonal media of the internet, email and IM (Instant Messenger). The analysis has been performed on two levels, first through examination of existing studies on this subject, and second, trough a survey on communicational use of the internet in Serbia, conducted in the period 2011-2012. on the sample of 1063 respondents and through 15 indepth interviews. The obtained results are similar to those from the vast body of other research, meaning that the internet doesn’t replace FtF contacts, but also that the internet`s interpersonal media are becoming more and more important in handling some aspects of personal networks connections. [Projekat Ministarstva nauke Republike Srbije, br. 36022]